Synthesis of spiro[dihydropyridine-oxindoles] via three-component reaction of arylamine, isatin and cyclopentane-1,3-dione - Sun, Yan; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2013)
A fast and convenient protocol for the synthesis of novel spiro[dihydropyridine-oxindole] derivatives in satisfactory yields was developed by the three-component reactions of arylamine, isatin and cyclopentane-1,3-dione in acetic acid at room temperature. On the other hand the condensation of isatin with two equivalents of cyclopentane-1,3-dione gave 3,3-bis(2-hydroxy-5-oxo-cyclopent-1-enyl)oxindole in high yields. The reaction mechanism and substrate scope of this novel reaction is briefly discussed.
Keywords: arylamine; cyclopentanedione; isatin; multicomponent reaction; spiro compound

(untitled) - Tan, B.; Hernández-Torres, G.; Barbas, C. F., III (J. Am. Chem. Soc., 2011)

(untitled) - Bazgir, A.; Noroozi Tisseh, Z.; Mirzaei, P. (Tetrahedron Lett., 2008)

(untitled) - Jadidi, K.; Ghahremanzadeh, R.; Bazgir, A. (Tetrahedron, 2009)

(untitled) - Badillo, J. J.; Arevalo, G. E.; Fettinger, J. C.; Franz, A. K. (Org. Lett., 2011)

(untitled) - Esmaeili, A. A.; Vesalipoor, H.; Hosseinabadi, R.; Zavareh, A. F.; Naseri, N. A.; Ghiamati, E. A. (Tetrahedron Lett., 2011)

(untitled) - Kiruthika, S. E.; Lakshmi, N. V.; Banu, B. R.; Perumal, P. T. (Tetrahedron Lett., 2011)

(untitled) - Shanmugam, P.; Viswambharan, B.; Madhavan, S. (Org. Lett., 2007)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Org. Lett., 2011)

(untitled) - Viswambharan, B.; Selvakumar, K.; Madhavan, S.; Shanmugam, P. (Org. Lett., 2010)

(untitled) - Quiroga, J.; Portillo, S.; Pérez, A.; Gálvez, J.; Abonia, R.; Insuasty, B. (Tetrahedron Lett., 2011)

(untitled) - Shakibaei, G. I.; Feiz, A.; Khavasi, H. R.; Soorki, A. A.; Bazgir, A. (ACS Comb. Sci., 2011)

(untitled) - Mohammadi, A. A.; Dabiri, M.; Qaraat, H. (Tetrahedron, 2009)

(untitled) - Basavaiah, D.; Reddy, K. R. (Org. Lett., 2007)

(untitled) - Liu, H.; Dou, D.; Shi, D. (J. Comb. Chem., 2010)

(untitled) - Sun, J.; Sun, Y.; Gao, H.; Yan, C.-G. (Eur. J. Org. Chem., 2012)

(untitled) - Joshi, K. C.; Jain, R.; Arora, S. (J. Fluorine Chem., 1989)

(untitled) - Dabiri, M.; Bahramnejad, M.; Baghbanzadeh, M. (Tetrahedron, 2009)

(untitled) - Ghahremanzadeh, R.; Ahadi, S.; Shakibaei, G. I.; Bazgir, A. (Tetrahedron Lett., 2010)

(untitled) - Ghahremanzadeh, R.; Shakibaei, G. I.; Ahadi, S.; Bazgir, A. (J. Comb. Chem., 2010)

(untitled) - Jadidi, K.; Ghahremanzadeh, R.; Bazgir, A. (J. Comb. Chem., 2009)

(untitled) - Kefayati, H.; Narchin, F.; Rad-Moghadam, K. (Tetrahedron Lett., 2012)

(untitled) - Ghahremanzadeh, R.; Fereshtehnejad, F.; Bazgir, A. (J. Heterocycl. Chem., 2010)

(untitled) - Rad-Moghadam, K.; Youseftabar-Miri, L. (Synlett, 2010)

(untitled) - Lu, G.-P.; Cai, C. (J. Chem. Res., 2011)

(untitled) - Rad-Moghadam, K.; Youseftabar-Miri, L. (J. Fluorine Chem., 2012)

(untitled) - Ghahremanzadeh, R.; Sayyafi, M.; Ahadi, S.; Bazgir, A. (J. Comb. Chem., 2009)

(untitled) - Bazgir, A.; Ahadi, S.; Ghahremanzadeh, R.; Khavasi, H. R.; Mirzaei, P. (Ultrason. Sonochem., 2010)

(untitled) - Khorrami, A. R.; Faraji, F.; Bazgir, A. (Ultrason. Sonochem., 2010)

(untitled) - Arya, K. A.; Kumar, M. (Mol. Diversity, 2011)

(untitled) - Stefanović, G.; Pavičić-Woss, M.; Lorenc, L.; Mihailović, M. L. (Tetrahedron, 1959)

(untitled) - Joshi, K. C.; Jain, R.; Arora, S. (Indian J. Heterocycl. Chem., 1991)

(untitled) - Dabiri, M.; Tisseh, Z. N.; Bahramnejad, M.; Bazgir, A. (Ultrason. Sonochem., 2011)

(untitled) - Ghahremanzadeh, R.; Fereshtehnejad, F.; Mirzaei, P.; Bazgir, A. (Ultrason. Sonochem., 2011)